Acceptability and Implementation Challenges of Benzathine Penicillin G Secondary Prophylaxis for Rheumatic Heart Disease in Ethiopia: A Qualitative Study - Eshetie Melese Birru; Kevin T. Batty; Laurens Manning; Stephanie L. Enkel; Brioni R. Moore (Global Heart)
Background: Monthly intramuscular injections of benzathine penicillin G (BPG) remain the cornerstone of secondary prophylaxis for acute rheumatic fever and rheumatic heart disease (RHD). The barriers to successful delivery of BPG may be patient- or service-delivery-dependent. Objective: The aim of the present study was to explore the perceived acceptability and implementation challenges of BPG treatment for RHD, from the perspective of healthcare providers (HCPs). Methodology: A descriptive qualitative study using semi-structured interview guides was conducted in four public hospitals in Ethiopia. Physicians and nurses who had at least 1 year of experience in delivering RHD secondary prophylaxis were recruited. The interviews were audio recorded, transcribed verbatim, and translated into English for analysis using framework method thematic analysis. Identified behavioral factors were mapped onto a theoretical framework of acceptability (TFA), and the Capability, Opportunity, Motivation-Behavior (COM-B) model. Result: Twenty-two interviews were conducted with HCPs (mean age 39 years, 55% nurses). Insights into BPG use and acceptability were categorized into four major themes related to: (1) individual factors (e.g., fear of anaphylactic reaction), (2) health system barriers (e.g., BPG shortage), (3) patient/caregiver perceptions (e.g., reliance on injectables, over expectation of treatment outcomes), and (4) product (e.g., injection pain, needle blockage). Conclusions: HCPs identified facilitators and barriers which highlight the complexities associated with BPG as secondary prophylaxis for RHD in Ethiopia. Based on these data, we suggest RHD control programs should (1) provide cross-disciplinary training and education programs to support safe and context-appropriate delivery of BPG (2) improve resourcing of health facilities to facilitate safe drug delivery, (3) establish a comprehensive system for auditing severe adverse reactions post-BPG injection to generate robust pharmacovigilance data, and consider alternative approaches to BPG delivery including access to improved formulations (e.g., BPG suspension formulations in pre-filled syringes). Highlights: • Key barriers included (a) resistance from healthcare providers to administer benzathine penicillin G (BPG) due to their concerns about injection-related severe adverse events, and potential repercussions should an event occur, (b) poor community and healthcare provider awareness of the disease and its treatment, (c) lack of resources to manage adverse events, and (d) injection pain. • Key enablers included (a) perceived superior treatment benefits of BPG and (b) co-administration of lidocaine/analgesics to reduce injection pain. • Recommendations to address identified challenges include (a) improved training/education on RHD diagnosis, disease progression, and treatment, (b) improved access to supportive resources, (c) active adverse reaction monitoring and reporting, and (d) encouraging the provision/access of globally subsidized BPG suspension formulations in pre-filled syringes.